HANDWRITTEN COPIES OF THE EPIC "TAHIR AND ZUHRA" - Mamatqulova Feruza Tohirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about the wide popularity of the Tahir and Zuhra epic in Khorezm and about similar and different aspects of the Tahir and Zuhra epic attributed to the Turkmen poet Mullanafas.